Controllable Synthesis and Characterization of SnS Nanostructures - Sohila*, S.; Ramesh, R.; Muthamizhchelvan*, C.; Ponnusamy, S. (Asian Journal of Chemistry, 2013)
SnS nanostructures (nanoparticles, nanosheets and nanorods) have been synthesized via solvothermal method. The morphology evolution of SnS nanostructures was obtained by changing the reaction time and keeping other parameters as constant. Phase purity of the synthesized samples was confirmed by powder X-ray diffraction pattern, which shows orthorhombic structure. The influence of reaction time on the morphology of SnS nanostructures were studied by transmission electron microscope. The morphology evolution of SnS nanoparticles is due to the selective adsorption of ethylene glycol on certain crystallographic facet in order to minimize the surface energy resulting one directional growth of the nanoparticles.